ESTUDO QUÍMICO E AVALIAÇÃO DAS ATIVIDADES BIOLÓGICAS DE EUGENIA PRUNIFORMIS CAMBESS (MYRTACEAE) - Martins, Fernanda Leite Pereira (2020)
Brazil is one of the countries with the greatest biodiversity in the world. The Myrtaceae family is one of the most representative of native Brazilian species. In Espírito Santo 52 species are found in the restinga vegetation regions inserted in the munic